Purchase Decision on Halal Products among Female Muslim: Evidence from Indonesia - Rusny Istiqomah Sujono; Wawan Wiyandi; Febrian Wahyu Wibowo; Ahmad Yunadi; Al Haq Kamal; Ardy Wibowo; Abdul Salam (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
So far, limited research has analyzed the factors influencing female's decisions to purchase halal products. The purpose of this study was to determine how religiosity, product quality, price, brand, and halal knowledge affect the decision-making process of Islamic female students when purchasing halal-certified products. The study employed quantitative research methods, employing a questionnaire distributed through Google Forms for data collection. The study's population comprised all female students at Pondok Pesantren Al Munawwir Yogyakarta Indonesia. The sampling technique employed the Slovin formula, resulting in a research sample of 91 respondents. Data analysis involved classical assumption tests, multiple linear regression, partial tests (t-tests), simultaneous tests (F-tests), and the determination coefficient (RÂ²). The findings indicated that religiosity, price, and halal knowledge negatively influenced female's purchasing decisions for halal products. Conversely, product quality and brand positively influenced these decisions. The study highlights that consumers, especially female students, prioritize brands and product quality when deciding to purchase halal products. Consequently, producers of halal products need to prioritize and enhance product quality.